CBD attenuates amygdala response to negative emotional stimuli in individuals with alcohol use disorder: a randomized controlled trial - Pfisterer, Marlen; Teetzmann, Anton; Vetter, Sina; Baeßler, Joscha; Schreckenberger, Lena; Zaiser, Judith; Stenger, Manuel; Bach, Patrick (Psychopharmacology, 2025)
Negative affect is a key factor in Alcohol Use Disorder (AUD) associated with craving and relapse risk that is insufficiently treated by approved medications. Cannabidiol (CBD) has shown promising effects on negative affect, indicating its potential for addressing the neurocircuitry underlying negative affect in AUD.
Gesehen am 28.10.2025